Influenza AH1N1 2009 pneumonia in kidney transplant recipients: Characteristics and outcomes following high-dose oseltamivir exposure - S. P. Watcharananan (2018)
We report 2 cases of severe pneumonia due to the novel pandemic influenza AH1N1 2009 in kidney transplant recipients. Our patients initially experienced influenza-like illness that rapidly progressed to severe pneumonia within 48 h. The patients became hypoxic and required non-invasive ventilation. The novel influenza AH1N1 2009 was identified from their nasal swabs. These cases were treated successfully with a relatively high dose of oseltamivir, adjusted for their renal function. Clinical improvement was documented only after a week of antiviral therapy. Despite early antiviral treatment, we showed that morbidity following novel pandemic influenza AH1N1 2009 infection is high among kidney transplant recipients. © 2010 John Wiley & Sons A/S.